Tropospheric clouds in Antarctica - Bromwich, David (author); Nicolas, Julien (author); Hines, Keith (author); Kay, Jennifer (author); Key, Erica (author); Lazzara, Matthew (author); Lubin, Dan (author); McFarquhar, Greg (author); Gorodetskaya, Irina (author); Grosvenor, Daniel (author); Lachlan-Cope, Thomas (author); van Lipzig, Nicole (author) (Reviews of Geophysics, 2012)
Compared to other regions, little is known about clouds in Antarctica. This arises in part from the challenging deployment of instrumentation in this remote and harsh environment and from the limitations of traditional satellite passive remote sensing over the polar regions. Yet clouds have a critical influence on the ice sheet's radiation budget and its surface mass balance. The extremely low temperatures, absolute humidity levels, and aerosol concentrations found in Antarctica create unique conditions for cloud formation that greatly differ from those encountered in other regions, including the Arctic. During the first decade of the 21st century, new results from field studies, the advent of cloud observations from spaceborne active sensors, and improvements in cloud parameterizations in numerical models have contributed to significant advances in our understanding of Antarctic clouds. This review covers four main topics: (1) observational methods and instruments, (2) the seasonal and interannual variability of cloud amounts, (3) the microphysical properties of clouds and aerosols, and (4) cloud representation in global and regional numerical models. Aside from a synthesis of the existing literature, novel insights are also presented. A new climatology of clouds over Antarctica and the Southern Ocean is derived from combined measurements of the CloudSat and Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) satellites. This climatology is used to assess the forecast cloud amounts in 20th century global climate model simulations. While cloud monitoring over Antarctica from space has proved essential to the recent advances, the review concludes by emphasizing the need for additional in situ measurements.